2010
DOI: 10.1103/physrevb.82.014412
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring tunnel magnetoresistance by ultrathin Cr and Co interlayers: A first-principles investigation of Fe/MgO/Fe junctions

Abstract: We report on systematic ab-initio investigations of Co and Cr interlayers embedded in Fe(001)/MgO/Fe(001) magnetic tunnel junctions, focusing on the changes of the electronic structure and the transport properties with interlayer thickness. The results of spin-dependent ballistic transport calculations reveal options to specifically manipulate the tunnel magnetoresistance ratio. The resistance area products and the tunnel magnetoresistance ratios show a monotonous trend with distinct oscillations as a function… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 47 publications
1
6
0
Order By: Relevance
“…Because of this, the areas of higher transmission when using Co electrodes lead to a finite G AP comparable to Fe that decreases its TMR. Previous first-principles studies have also found a higher TMR using bcc Fe compared to bcc Co electrodes 27 , confirming that the k || = 0 are important. Previous theoretical and experimental work has found higher TMR when adding bcc Co interlayers between the bcc Fe electrode and MgO barrier 10,13 , however our present results suggest a pure bcc Co electrode will not necessarily improve TMR.…”
Section: A Vca Transportsupporting
confidence: 63%
“…Because of this, the areas of higher transmission when using Co electrodes lead to a finite G AP comparable to Fe that decreases its TMR. Previous first-principles studies have also found a higher TMR using bcc Fe compared to bcc Co electrodes 27 , confirming that the k || = 0 are important. Previous theoretical and experimental work has found higher TMR when adding bcc Co interlayers between the bcc Fe electrode and MgO barrier 10,13 , however our present results suggest a pure bcc Co electrode will not necessarily improve TMR.…”
Section: A Vca Transportsupporting
confidence: 63%
“…The observed is much longer than the theoretical value of 0.7 # A at t MgO ¼ 6 ML (%12:1 # A) and 2.1 # A at t MgO ¼ 10 ML. 23,25) The long could be partly due to the roughness of the Cr layer in type-A MTJs. However, a similar long was also obtained in type-B MTJs.…”
Section: Resultsmentioning
confidence: 99%
“…In the phenomenological model, we neglect the influence of the Cr/Fe interface because it should have little influence on the parallel conductance. 23) For simplicity, the model does not take the scattering at the bottom interface into account. Thus, the current through the transport channels 1), 4), and 5) are regarded as the coherent current (I coh ), and the current through the transport channels 2), 3), and 6) are regarded as the incoherent current (I inc ).…”
Section: Appendixmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, small structural randomness at the Fe/MgO interface can also significantly reduce the TMR ratio [10]. Several methods such as introducing boron into the electrode or inserting a metal interlayer at the interface are used to improve the quality of the ferromagnet (FM)/MgO interface [11][12][13]. The introduction of B can effectively reduce the FM/MgO interface roughness [14], prevent interfacial oxidation [15], and reduce passive oxygen vacancies in MgO through B diffusion [16][17][18].…”
Section: Introductionmentioning
confidence: 98%